Perancangan Safety Signs Menggunakan Safety Signs Assessement dan Pendekatan Quality Function Deployment untuk Mengendalikan Risiko Keselamatan dan Kesehatan Kerja di PT.XYZ - Shakila Hamidi; Heriyono Lalu; Sheila Amalia Salma (Peneliti.net, 2022)
PT XYZ is a company engaged in the furniture industry where this companyprocesses raw materials into furniture products that have added value andhave benefits from before. In its operational activities, the company still hasnot implemented a good occupational health and safety system because of themany risks that must be faced by workers. This can be seen from the numberof hazard events found during the production process. Based on the resultsof field observations, there are 9 hazard events where these incidents must beminimized in order to reduce the number of work accidents. Risk control isone of the first steps used in minimizing the occurrence of hazards byanalyzing the risk control hierarchy. Analysis of the Risk Control Hierarchyis a form of process in analyzing the proposed K3 control in every event thatoccurs. The results of the risk control hierarchy analysis are suggestions foreach hazard event that have been adjusted to the level of the risk controlhierarchy. Of all the potential proposals given, some can be forwarded to thedesign in the form of providing safety signs in 2 hazard areas, namely theforklift area, slippery work area and smoke-free area. Before designing asafety sign, it is necessary to first evaluate the safety sign. Assessment ofsafety signs is an activity to assess the conditions or conditions of the fieldwhere safety signs will be installed to be able to find out the requirements orcriteria for appropriate safety signs in the hazard area. And from this processit can be known about the installation location of safety signs, Signal Wordsto be used, height, model, minimum reading distance and materials used inthe design of safety signs. The data used is anthropometric data that has beenfiltered according to the criteria of users who will read Safety Signs. Afterevaluating the safety sign, the next step is to make a design using the QualityFunction Deployment approach. QFD is a solution to design or develop aproduct in a structured manner by determining in advance the needs ordesires of the target consumer in advance so that they are able to take intoaccount systematically. In designing QFD there are 11 stages to be carriedout. The results of the QFD are the final specifications that become thereference in designing safety signs. have carried out a safety sign assessmentand Quality Function Deployment, the next step is to design a Safety sign thatrefers to the ANSI Z535.4 standard. The results of the design are in the formof a safety sign design that will be placed in the forklift area and a safety signdesign that will be placed in a slippery area.